Financial Inclusion Index for Pakistan from 2008 to 2022 using Three-Staged PCA Analysis - Ansari, Ammad; Dr. Salman Ali Qureshi (UW Journal of Management Sciences, 2024)
Purpose: This study aims to develop a Financial Inclusion Index (FI Index) for Pakistan from 2008 to 2022, utilizing a three-stage Principal Component Analysis (PCA) technique. It evaluates the progress in both traditional and digital financial inclusion. Design and Methodology: The FI index was constructed using supply-side indicators (e.g., bank branches, ATMs, mobile subscriptions) and demand-side variables (e.g., account ownership, savings behavior, mobile payments). Sub-indices for traditional and digital financial inclusion were combined to form a comprehensive index. Findings: The results indicate significant improvements in financial inclusion in Pakistan, particularly in digital services, though challenges remain in integrating underserved populations. Implications: The developed FI index provides valuable insights for policymakers to design strategies that promote inclusive financial systems, contributing to sustainable economic growth. Keywords: Financial Inclusion (FI), Financial Inclusion Index (FI Index), Principal Component Analysis (PCA), Composite FI Index, Traditional Index, Digital Index.